A method of product feature usability analysis based on web semantic mining. (15th January 2013) - Long, Huijun; Wang, Liya; Liu, Pan
Product usability is an evaluation indicator of customer satisfaction with product features and functions. Questionnaire survey is traditional methods widely used in product feature usability analysis. In fact, it is labour intensive and time consuming. Nowadays, with the rapid expansion of web, more and more customers tend to express their opinions on products through it. As a result, the number of reviews on certain product grows rapidly. This paper proposes a novel method based on web semantic mining of Chinese customer reviews to analyse product feature usability. First, useful information corresponding to product feature usability, such as customers' reviews of products, is extracted from webs based on the semantic mining technology with an information system, called Web Miner. Then the product feature usability is measured and evaluated by evaluation model. Finally, usability analysis of Nokia 5230 is used as a case to validate the proposed method.